2017
DOI: 10.1108/oir-02-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Proactive disclosure of public information: legislative choice worldwide

Abstract: Purpose The purpose of this paper is twofold: to identify legislators’ policy on the mandatory, online proactive disclosure of information; and to identify environmental influences on behaviour in this respect. To implement these proactive policies on transparency included in the legislative frameworks, internet websites are being used as a means of disseminating this proactive information. Design/methodology/approach To achieve these goals, by application of the theories used to analyse the causes of inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…Research (Alcaide- Muñoz et al, 2017;García-Tabuyo, Saez-Martin, and Caba-Perez, 2017;Sáez-Martín et al, 2017) has showed that there is a positive relationship between municipal wealth and the online disclosure of public information and transparency. We will test hypotheses H 3.1. and H 3.2 as summarised in Table 1.…”
Section: Population Density (Den)mentioning
confidence: 99%
“…Research (Alcaide- Muñoz et al, 2017;García-Tabuyo, Saez-Martin, and Caba-Perez, 2017;Sáez-Martín et al, 2017) has showed that there is a positive relationship between municipal wealth and the online disclosure of public information and transparency. We will test hypotheses H 3.1. and H 3.2 as summarised in Table 1.…”
Section: Population Density (Den)mentioning
confidence: 99%
“…The most often used data from the years 2008, 2010 and 2012, and there were no papers that used data from the last 3 years (2017-2019). The year of publication of the most recent paper in the sample is 2019, however the one that used the most recent data was García-Tabuyo et al (2017), who used data from 2016.…”
Section: Inherent Characteristicsmentioning
confidence: 99%
“…One of the government's obligations in serving the community is to provide clear and concise information (Kurniawan et al, 2017). This corresponds to the purpose of the issuance of the Republic of Indonesia Presidential Instruction No 3 of 2003 concerning National Policies and Strategies for E-government Development that online information disclosure will encourage governments to make clear transparency and act for the public interest (García-Tabuyo et al, 2017). Therefore, it can be stated that information disclosure, both through regulations and online, is critical to deterring corruption in Indonesia.…”
Section: Strategy To Mitigate Corruption In the Indonesian Provincesmentioning
confidence: 99%